Caregivers’ and healthcare professionals’ perspective of barriers and facilitators to health service access for asthmatic children: a qualitative study - Cristina Ardura-Garcia; Philip J Cooper; John D Blakey; Natalia Romero-Sandoval (BMJ Open Respiratory Research)
Background There is a high burden of asthma morbidity and mortality in Latin America. It has been proposed that this relates to limited access to diagnostic tests, asthma medications and specialised doctors. However, little is known of what caregivers of asthmatic children and healthcare professionals (HCPs) perceive as barriers and facilitators to adequate care. We aimed to explore the barriers and facilitators to asthma care access from caregivers’ and HCP’s perspective in an Ecuadorian low-resource setting.Methods In 2017, we conducted 5 focus group discussions (FGD) with 20 caregivers of asthmatic children and 12 in-depth interviews with 3 paediatricians, 6 general doctors and 3 respiratory therapists in Esmeraldas city, Ecuador. FGDs and interviews were digitally recorded, transcribed, open-coded in QDA Miner, categorised using an interpretative phenomenological approach and analysed thematically. Barriers and facilitators were classified into availability, accessibility, acceptability and contact of healthcare services, based on Tanahashi model of health service access.Results Limited resources, use of alternative medicines, fear of medication side-effects and lack of specific training for doctors and knowledge in families were common barriers for both caregivers and HCPs. Caregivers and HCPs proposed the implementation of public health asthma-focused programmes that would include close community-based follow-up of people with asthma, educational sessions for their families and public engagement activities. HCPs also suggested implementing training programmes on asthma management for general doctors.Conclusion Multiple barriers identified by caregivers and HCPs referred to economic and health service organisational issues, fear of side effects of medication or ineffective self-management. Increasing caregivers and HCPs’ asthma knowledge, as well as HCPs’ communication skills to establish a patient-centred approach with a shared decision-making process could improve asthma care in this setting.